2019
DOI: 10.1101/592964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Mechanistic Contribution of Herbal Extracts in Compound Kushen Injection with Transcriptome Analysis

Abstract: Running title: Identification of herbal compatibility mechanisms with transcriptome data AbstractHerbal compatibility is the knowledge of which herbs to combine in traditional Chinese medicine (TCM) formulations. The lack of understanding of herbal compatibility is one of the key problems for the application and popularization of TCM in western society. Because of the chemical complexity of herbal medicines, it is simpler to begin to conduct compatibility research based on herbs rather than component plant sec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Kushen has a long history of being used for the treatment of solid tumors, inflammation and other diseases, such as gynecological diseases [10]. Studies have found that Baituling can not only enhance the cytotoxicity of Kushen in CKI, but also activate immune-related pathways [11]. CKI mainly contains various anticancer ingredients such as matrine and oxymatrine, which can inhibit tumor cell growth, induce the apoptosis of cancer cells, and resist cancer cell metastasis, and is unsusceptible to multidrug resistance and protective against overactive immune responses in the body [12].…”
Section: Introductionmentioning
confidence: 99%
“…Kushen has a long history of being used for the treatment of solid tumors, inflammation and other diseases, such as gynecological diseases [10]. Studies have found that Baituling can not only enhance the cytotoxicity of Kushen in CKI, but also activate immune-related pathways [11]. CKI mainly contains various anticancer ingredients such as matrine and oxymatrine, which can inhibit tumor cell growth, induce the apoptosis of cancer cells, and resist cancer cell metastasis, and is unsusceptible to multidrug resistance and protective against overactive immune responses in the body [12].…”
Section: Introductionmentioning
confidence: 99%
“…This manuscript has been released as a BioRxiv pre-print (MS ID #BIORXIV/2019/592964) at: https://www.biorixiv.org/content/10.1101/59294v1 (33).…”
mentioning
confidence: 99%
“…As a mixture of oligomers, the compound peaks of P80 are highly overlapped in 1 H NMR spectroscopy and the corresponding numbers of protons are difficult to determine. 26 Therefore, the external standard curve was applied to quantify P80.…”
Section: Quantificationmentioning
confidence: 99%
“…Given that most of the components in CHIs are proton-containing organics, some researchers have proposed the potential of the proton nuclear magnetic resonance ( 1 H NMR) method for the comprehensive composition characterisation of CHIs. 5,6 As an untargeted approach, 1 H NMR spectroscopy provides access to detect all proton-bearing compounds irrespective of their chemical characteristics, with the advantage of non-destructive sample preparation, informative spectral patterns, simple operation, and high-throughput acquisition. 11 Thus, 1 H NMR is widely used in metabolic profiling of complex mixtures, such as biological samples, 12,13 foods, [14][15][16] herbal medicine, 11,17 and environmental samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation